Constraining the formation of authigenic carbonates in a seepage‐affected cold‐water coral mound by lipid biomarkers. Issue 2 (3rd February 2020) - Feenstra, Eline Juliette; Birgel, Daniel; Heindel, Katrin; Wehrmann, Laura M.; Jaramillo‐Vogel, David; Grobéty, Bernard; Frank, Norbert; Hancock, Leanne G.; Van Rooij, David; Peckmann, Jörn; Foubert, Anneleen
Abstract: Cold‐water coral (CWC) mounds are build‐ups comprised of coral‐dominated intervals alternating with a mixed carbonate‐siliciclastic matrix. At some locations, CWC mounds are influenced by methane seepage, but the impact of methane on CWC mounds is poorly understood. To constrain the potential impact of methane on CWC mound growth, lipid biomarker investigations were combined with mineralogical and petrographic analyses to investigate the anaerobic oxidation of methane (AOM) and authigenic carbonate formation in sediment from a seep‐affected CWC mound in the Gulf of Cadiz. The occurrence of AOM was confirmed by characteristic lipids found within a semi‐lithified zone (SLZ) consisting of authigenic aragonite, high‐magnesium calcite and calcium‐excess dolomite. The formation of high‐Mg calcite is attributed to AOM, acting as a lithifying agent. Aragonite is only a minor phase. Ca‐excess dolomite in the SLZ and upper parts may be formed by organoclastic sulphate reduction, favouring precipitation by increased alkalinity. The AOM biomarkers in the SLZ include isoprenoid‐based archaeal membrane lipids, such as abundant glycerol dibiphytanyl glycerol tetraethers (GDGTs) dominated by GDGT‐2. The δ 13 C values of GDGT‐2, measured as ether‐cleaved monocyclic biphytanes, are as low as −100‰ versus V‐PDB. Further, bacterial dialkyl glycerol diethers with two anteiso ‐C15 alkyl chains and δ 13 C values of −81‰ are interpreted as biomarkers of sulphate‐reducing bacteria. The lipid biomarker signatures and mineralogical patterns suggest that anaerobic methane‐oxidizing archaea of the ANME‐1 group thrived in the subsurface at times of slow and diffusive methane seepage. Petrographic analyses revealed that the SLZ was exhumed at some point (e.g. signs of bioerosion of the semi‐lithified sediment), providing a hard substrate for CWC larval settlement. In addition, this work reveals that AOM‐induced semi‐lithification likely played a role in mound stabilization. Lipid biomarker analysis proves to be a powerful tool to disentangle early diagenetic processes induced by microbial metabolisms.